Plastic and Reconstructive Surgery - Siemionow, Maria Z.; Eisenmann-Klein, Marita; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
Plastic and Reconstructive Surgery, edited by Maria Siemionow and Marita Eisenmann-Klein, is the latest in a long line of highly valued texts found in the Springer Specialist Surgical Series. Plastic and Reconstructive Surgery brings an up-to-date comprehensive review of the basics of physiology and wound healing, and both standard and new techniques and technologies introduced in recent years to plastic surgery. It provides a fast and comprehensive overview of plastic surgery to help residents and young plastic surgeons to prepare for board exams in one succinct volume of plastic surgery knowledge. The book is divided into seven major categories. In each category, chapters related to anatomy, physiology and pathology are supplemented with chapters on treatment options including conventional surgical techniques as well as new technical approaches including endoscopic and minimally invasive surgery. The chapters are designed to address questions most often asked on the specialty boards. The book summarizes basic plastic surgery knowledge in the light of innovations and new technologies as well as research approaches as applied to general plastic, hand surgery, peripheral nerve surgery, microsurgery, breast surgery, esthetic surgery, and reconstructive surgery. Using a multidisciplinary approach, presentation of the basic plastic surgery knowledge encompasses areas worthy not only of attention from plastic surgeons but also hand, microsurgeons, head and neck specialists, and breast surgeons. Maria Z. Siemionow, MD, PhD, DSc, Professor of Surgery, Director of Plastic Surgery Research, Head of Microsurgery Training, Department of Plastic Surgery, Cleveland Clinic Foundation, Cleveland, OH, USA. Marita Eisenmann-Klein MD, Deputy General Secretary of the International Confederation of Plastic Reconstructive and Aesthetic Surgery, Director, Department of Plastic and Aesthetic, Hand and Reconstructive Surgery, Caritas-Krankenhaus St. Josef, Regensburg, Germany
General Principles -- Physiology and Wound Healing -- Immunology of Tissue Transplantation -- Anesthesia and Critical Care -- Medical Liability in Plastic and Reconstructive Surgery -- Sociopsychological Issues and Research on Attractiveness -- General Surgical Techniques -- Principles of Wound Repair -- Grafts, Local and Regional Flaps -- Microsurgical Techniques -- Minimally Invasive Techniques in Plastic Surgery -- Liposuction Techniques -- Biomaterials in Craniofacial Surgery -- Tissue Engineering -- Skin and Adnexa -- Skin Anatomy and Physiology -- Congenital Malformations -- Burn Trauma -- Benign and Malignant Skin Tumors -- Esthetic Skin Treatments (Fillers) -- Head and Neck -- Head and Neck Embryology and Anatomy -- Craniofacial Clefts and Craniofacial Syndromes -- Benign and Malignant Tumors of the Head and Neck -- Craniofacial Trauma and Reconstruction -- Eyelid and Periorbital Aesthetic Surgery -- Nasal Reconstruction and Aesthetic Rhinoplasty -- Lip and Cheek Reconstruction -- Auricular Reconstruction for Microtia -- Aesthetic Surgery of the Aging Face and Neck -- Treatment of Headaches with Plastic Surgery -- Facial Reanimation -- Breast -- Congenital Breast Malformations -- Breast Reduction and Mastopexy -- Postmastectomy Breast Reconstruction -- Augmentation Mammoplasty -- Gynecomastia -- Hand and Upper Extremity -- Hand Anatomy and Examination -- Congenital Deformities and Reconstruction -- Hand Trauma, Dislocations and Fractures, Infections -- Peripheral Nerve Injuries -- Tendon Repair and Reconstruction -- Benign and Malignant Hand Tumors -- Chronic Arterial Ischemia of the Upper Extremity: Diagnosis, Evaluation, and Surgical Management -- Acquired Diseases of the Hand (Rheumatoid Arthritis and Dupuytren's Contracture) -- Toe-to-Hand Transfers -- Brachial Plexus Injuries and Repair -- Trunk and Lower Extremity -- Trunk Reconstruction -- Lower Extremity Reconstruction Following Trauma and Tumors -- Abdominoplasty -- Lymphedema of the Extremities -- Postbariatric Reconstruction -- Reconstructive and Aesthetic Surgery of the Genitalia -- Future Directions in Research -- Anesthesia and Pathophysiology of Microcirculation -- Experimental Composite Tissue Transplantation Models -- Clinical Experience with Hand Transplantation.
Keywords: Medicine; Surgery; Medicine & Public Health; Plastic Surgery; Surgery